TUDY ON CONVENTIONAL AND NOVEL CARDIAC BIOMARKERS IN ACUTE MYOCARDIAL INFARCTION - Kumar, Munta Anil; Swamy, Raji; ., Ramaswamy (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Employment of the serum cardiac markers rather than noninvasive or invasive procedures in the right time for accurate diagnosis of acute myocardial infarction (AMI) is a more important to restore the patient, but using all of them is inappropriate and expensive. Therefore, this study is designed to determine promising marker for the diagnosis of AMI. Methods: A total of 33 healthy volunteers and 42 AMI patients were enrolled, and the serial blood samples were obtained from the AMI patients at admission, 6 th , 12 th , 24 th , and 48 hr from the time of onset. The diagnostic efficiency was determined for creatine kinase (CK), CK MB (CK-MB), N-terminal fragment of B-type natriuretic peptide (NTproBNP), high sensitive cardiac troponin I (hscTnI), ischemia modified albumin (IMA), heart-type fatty acid binding protein (H-FABP), and myoglobin using receiving operating characteristic (ROC) curves and compared for time periods. th Results: Lipid profile, fasting blood sugar (FBS), creatinine, alanine transaminase (ALT), and aspartate transaminase (AST) were significantly higher in AMI when compared to control. In the early stages of AMI, the ROC of H-FABP (0.89; 95% confidence interval [CI], 0.72-0.82), IMA (0.83; 95% CI, 0.74-0.90), hscTnI (0.81; 95% CI, 0.75-0.92), NTproBNP (0.82; 95% CI, 0.72-0.89) and myoglobin (0.86; 95% CI, 0.76-0.93), and displayed good diagnostic efficacy (p<0.0001). Conclusion: Within 2-6 hrs from onset of the symptoms, H-FABP, IMA and Myoglobin showed good diagnostic ability and in the entire episode, hscTnI holds its superiority in the diagnosis of AMI. Keywords: Acute myocardial infarction, Serum cardiac markers, Serial sampling, Diagnostic ability. Â 